Pengaruh Literasi Membaca Cerita Pendek Terhadap Pengembangan Kosakata Siswa Sekolah Dasar - Misriandi Misriandi; Galih Maulana Hendrawan (Universitas Palangka Raya, 2024)
This research was motivated by the low level of vocabulary development among students, making it difficult for students to understand reading written texts and hampering students' digestibility in understanding the contents of the text, especially in learning material. The research hypothesis is that there is an influence of short story reading literacy on the vocabulary development of grade IV elementary school students at SDN Duren Seribu 01. The aim of this research is to find out whether there is an influence of short story reading literacy on elementary school students' vocabulary development. This research was carried out at SDN Diren Seribu 01, Duren Seribu Village, Bojongsari District, Depok City. The research population used in this research was class IV C with a sample of 29 students. The instrument given is a description test with a total of 10 questions to develop students' vocabulary. This research was conducted with pre-experimental research using a quantitative approach method. The data collection techniques used in this research were observation, tests, and documentation. Success in this research was proven by the T test with results showing 0.000 < α (0.05). Thus it can be concluded that there is an influence of literacy in reading short stories on vocabulary development. student.